Quantification of bone histomorphometric parameters using the Weibel technique in animals - Saif Am; Norazlina Mohamed; Ima-Nirwana Soelaiman (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Bone histomorphometric measurements are required to understand the efficacy of treatment on bone remodelling. Previous studies used the Weibel technique as a quantitative stereological method to determine bone cellular and dynamic changes. However, there was no description on how this technique was applied. This studyaimed to provide a full picture about the utilization of the Weibel technique to measure static and dynamic bone histomorphometric indices. Technical expertise, processing of bone samples, randomization of the trabecular sections and an adequate number of analysed images for each section are required to achieve reliable results with a low possibility of errors.